2022
DOI: 10.3390/plants11030310
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Assessment of Grassland Dynamic and Its Response to Drought Based on Multi-Index in the Mongolian Plateau

Abstract: This study applied grassland related multi-index and assessed the effects of climate change by investigating grassland responses to drought. This process was performed to study grassland vegetation dynamic accurately and evaluate the effect of drought in the Mongolian Plateau (MP). The spatial–temporal characteristics of grassland dynamic in terms of coverage (Fv), surface bareness (Fb), and net primary production (NPP) from 2000 to 2013 were explored. We implemented the maximum Pearson correlation to analyze … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
0
1
0
Order By: Relevance
“…In the Mongolian Plateau, vegetation change is strongly affected by climate change and human activities (Meng et al, 2019). During the past decades, overgrazing and mining are the main drivers for grassland degradation in Mongolia (Zhang et al, 2022b). In China, grassland restoration has been implemented over the past decades (Cai et al, 2020;Wei et al, 2023).…”
Section: The Climate Factors Driving Gpp and Lai Changes Were Dividedmentioning
confidence: 99%
“…In the Mongolian Plateau, vegetation change is strongly affected by climate change and human activities (Meng et al, 2019). During the past decades, overgrazing and mining are the main drivers for grassland degradation in Mongolia (Zhang et al, 2022b). In China, grassland restoration has been implemented over the past decades (Cai et al, 2020;Wei et al, 2023).…”
Section: The Climate Factors Driving Gpp and Lai Changes Were Dividedmentioning
confidence: 99%
“…Zhang and Wang et al, (2022) [ 2 ] investigated the responses of plants, soil bacteria, and fungal diversity to climate change (especially rainfall patterns and air temperature) in the desert grassland of the Ningxia Hui Autonomous Region of China. The results indicated that increased precipitation promoted root biomass growth more than aboveground living biomass, and changing precipitation and increasing temperature, as well as their interaction, primarily altered the plant diversity, soil bacteria and fungal diversity but had no significant impact on plant biomass production, organic carbon, total nitrogen and total phosphorus contents of plants.…”
mentioning
confidence: 99%